2021
DOI: 10.6060/ivkkt.20216407.6409
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-solution synthesis of iron (III) oxide

Abstract: Исследован процесс образования нерастворимых соединений железа, инициируемый действием разряда постоянного тока атмосферного давления в воздухе на водный раствор сульфата железа (III). Было обнаружено, что, когда раствор является анодом, действие разряда приводит к образованию коллоидного раствора гидроксосульфатов железа и гидроксида железа. Коллоидный раствор, как показывает метод DLS, состоит из двух фракций размером 47 нм (73%) и 950 нм. Кинетику образования коллоидных частиц исследовали турбодиметрическим… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…But EDS analysis showed that the composition of the substance can be described as 0.46 • Co(OH) 2 :0.54 • Co(OH) 3 (molar ratio). Note that the closest relative of cobalt in the periodic table (iron) also forms amorphous precipitates when a discharge acts on its aqueous solutions [24,25]. The TGA and DSC analysis data (figure 8) do not contradict the above-mentioned composition of the product.…”
Section: Resultsmentioning
confidence: 74%
“…But EDS analysis showed that the composition of the substance can be described as 0.46 • Co(OH) 2 :0.54 • Co(OH) 3 (molar ratio). Note that the closest relative of cobalt in the periodic table (iron) also forms amorphous precipitates when a discharge acts on its aqueous solutions [24,25]. The TGA and DSC analysis data (figure 8) do not contradict the above-mentioned composition of the product.…”
Section: Resultsmentioning
confidence: 74%